Green nanotechnology for controlling bacterial load and heavy metal accumulation in Nile tilapia fish using biological selenium nanoparticles biosynthesized by Bacillus subtilis AS12 - Saad, Ahmed M.; Sitohy, Mahmoud Z.; Sultan-Alolama, Mohamad I.; El-Tarabily, Khaled A.; El-Saadony, Mohamed T. (Frontiers in Microbiology, 2022)
Heavy metal accumulation and pathogenic bacteria cause adverse effects on aquaculture. The active surface of selenium (Se) nanoparticles can mitigate these effects. This study used Se-resistant Bacillus subtilis AS12 to fabricate biological Se nanoparticles (Bio-SeNPs). The double-edged Bio-SeNPs were tested for their ability to reduce the harmful effects of heavy metals and bacterial load in Nile tilapia (Oreochromis niloticus) and their respective influences on fish growth, behavior, and health. The Bio-SeNPs have a spherical shape with an average size of 77 nm and high flavonoids and phenolic content (0.7 and 1.9 g g-1 quercetin and gallic acid equivalents, respectively), resulting in considerable antioxidant and antibacterial activity. The Bio-SeNPs (3-5 µg ml-1) in the current study resolved two serious issues facing the aquaculture industry, firstly, the population of pathogenic bacteria, especially Aeromonas hydrophilia, which was reduced by 28-45 % in fish organs. Secondly, heavy metals (Cd, and Hg) at two levels (1 and 2 µg ml-1) were reduced by 50-87 % and 57-73 % in response to Bio-SeNPs (3-5 µg ml-1). Thus, liver function parameters were reduced, and inner immunity was enhanced. Water application content of Bio-SeNPs (3-5 µg ml-1) improved fish gut health, growth, and behavior, resulting in fish higher weight gain by 36–52% and a 40% specific growth rate, compared to controls. Furthermore, feeding and arousal times increased by 20–22 % and 28–53 %, respectively, while aggression time decreased by 78% compared to the control by the same treatment. In conclusion, Bio-SeNPs can mitigate the accumulation of heavy metals and reduce the bacterial load in a concentration-dependent manner, either in the fish media or fish organs.